Effect of high-valency pneumococcal conjugate vaccines on invasive pneumococcal disease in children in SpIDnet countries: an observational multicentre study - Savulescu, Camelia; Krizova, Pavla; Lepoutre, Agnes; Mereckiene, Jolita; Vestrheim, Didrik F; Ciruela, Pilar; Ordobas, Maria; Guevara, Marcela; McDonald, Eisin; Morfeldt, Eva; Kozakova, Jana; Varon, Emmanuelle; et al. (The Lancet. Respiratory medicine, 2017)
BACKGROUND: The Streptococcus pneumoniae Invasive Disease network (SpIDnet) actively monitors populations in nine sites in seven European countries for invasive pneumococcal disease. Five sites use 13-valent pneumococcal conjugate vaccine (PCV13) alone and four use the ten-valent PCV (PCV10) and PCV13. Vaccination uptake is greater than 90% in six sites and 67-78% in three sites. We measured the effects of introducing high-valency PCVs on the incidence of invasive pneumococcal disease in children younger than 5 years. METHODS: We compared the incidence of invasive pneumococcal disease in each of the 4 years after the introduction of PCV13 alone or PCV10 and PCV13 with the average incidence during the preceding period of heptavalent PCV (PCV7) use, overall and by serotype category. We calculated incidence rate ratios (IRRs) and 95% CIs for each year and pooled the values for all sites in a random effects meta-analysis. FINDINGS: 4 years after the introduction of PCV13 alone or PCV10 and PCV13, the pooled IRR was 0·53 (95% CI 0·43-0·65) for invasive pneumococcal disease in children younger than 5 years caused by any serotype, 0·16 (0·07-0·40) for disease caused by PCV7 serotypes, 0·17 (0·07-0·42) for disease caused by 1, 5, and 7F serotypes, and 0·41 (0·25-0·69) for that caused by 3, 6A and 19A serotypes. We saw a similar pattern when we restricted the analysis to sites where only PCV13 was used. The pooled IRR for invasive pneumococcal disease caused by non-PCV13 serotypes was 1·62 (1·09-2·42). INTERPRETATION: The incidence of invasive pneumococcal disease caused by all serotypes decreased due to a decline in the incidence of vaccine serotypes. By contrast, that of invasive pneumococcal disease caused by non-PCV13 serotypes increased, which suggests serotype replacement. Long-term surveillance will be crucial to monitor the further effects of PCV10 and PCV13 vaccination programmes in young children. FUNDING: European Centre for Disease Prevention and Control, Czech National Institute of Public Health, French National Agency for Public Health, Irish Health Services Executive, Norwegian Institute of Public Health, Public Health Agency of Catalonia, Public Health Department of Community of Madrid, Navarra Hospital Complex, Public Health Institute of Navarra, CIBER Epidemiology and Public Health, Institute of Health Carlos III, Public Health Agency of Sweden, and NHS Scotland.
Keywords: Immunization Programs; pneumokokové infekce; Incidence; kojenec; Europe; Evropa; Pneumococcal Infections; mužské pohlaví; Infant; incidence; Pneumococcal Vaccines; očkovací programy; Streptococcus pneumoniae; hodnocení výsledků zdravotní péče; Child, Preschool; ženské pohlaví; Humans; předškolní dítě; Outcome Assessment, Health Care; Female; pneumokokové vakcíny; lidé; Male